Answer:
{13, 23, 11, 16, 15, 10, 26}
Step-by-step explanation:
The "middle" of a sorted list of numbers. To find the Median, place the numbers in value order and find the middle number. Example: find the Median of {13, 23, 11, 16, 15, 10, 26}. The middle number is 15, so the median is 15.
plzzzz lmk if it was right and give me the brainliest
THX so muchhhhh
Answer:
The answer would be the last one. 18, 15, 11, 14, 19, 6
Here's Why:
To find the median, you must first put these numbers in order from least to greatest.
Least ----> Greatest
6, 11, 14, 15, 15, 18, 19
The next step is to find the middle number. In this case, the middle number is 15, therefore, you're median is 15.
6, 11, 14, 15, 15, 18, 19
(: hope this answers your question
An experiment consists of spinning a spinner. The table shows the results. Find the experimental probability that the spinner does not land on red. Express your answer as a fraction in simplest form.
Red: 10
Purple: 11
Yellow: 13
The experimental probability that the spinner does not land on red is 12/17.
Explanation:The question asks to find the experimental probability that a spinner does not land on red. To find this, we add the number of times the spinner landed on colors other than red and divide that sum by the total number of spins. In the given experiment, the spinner landed on purple 11 times and on yellow 13 times. Therefore, the total number of non-red outcomes is 11 (purple) + 13 (yellow) = 24.
The total number of spins is the sum of red, purple, and yellow outcomes: 10 (red) + 24 (non-red) = 34. The experimental probability of not landing on red is the number of non-red outcomes divided by the total number of spins, which gives us 24/34, which simplifies to 12/17.
Final answer:
The experimental probability that the spinner does not land on red is ⅔ or 12/17.
Explanation:
The question asks to find the experimental probability that the spinner does not land on red. To calculate this, we need to consider the total number of spins and the number of times the spinner did not land on red.
In this experiment, there were 10 instances of landing on red, 11 on purple, and 13 on yellow. To find the total number of spins, we add these together:
10 (red) + 11 (purple) + 13 (yellow) = 34 total spins
Now, to find the number of spins that did not land on red, we only consider the purple and yellow ones:
11 (purple) + 13 (yellow) = 24 non-red spins
The experimental probability is the number of non-red spins over the total number of spins:
Experimental probability = number of non-red spins / total number of spins = 24/34
To simplify this fraction, we divide both the numerator and the denominator by the greatest common factor, which is 2 in this case:
24 ÷ 2 = 12
34 ÷ 2 = 17
So, the probability in simplest form is:
Experimental probability = 12/17
A bacterium in a petri dish multiplies by a factor of 31 every day. On day O,
there is 1 bacterium; on day 1, there are 31 bacteria; on day 2, there are
bacteria; on day 3, there are
bacteria, and so on.
What logarithmic equation can be used to find the number of days it takes for
a colony of 1 bacteria to develop?
Answer:
Step-by-step explanation:
Given that,
The bacterial increase a factor of 31 every day ,
Day 0 = 1 bacterium = 31^0
Day 1 = 31 bacterial = 31¹
Day 2 = 31× 31 bacterial = 31²
Day 3 = 31 × 31 × 31 bacterial = 31³
And so on,
Then, nth day will have
Day n = 31ⁿ bacterial
So, when will the bacterial be 1,000,000,000
Then,
31ⁿ = 1,000,000,000
Take the Natural logarithmic to base 31 of both sides
Log_31 (31)ⁿ = Log_31 (1,000,000,000)
n•Log_31 (31) = Log_31 (1,000,000,000)
Then, log_a (a) = 1
n = Log_31 (1,000,000,000)
Check attachment for better view
Then,
The correct answer is A
The perimeter of a rectangular field is 368 yards. If the width of the field is 87 yards, what is it’s length
Answer: The length of the rectangle would be 97 yards.
Step-by-step explanation:
87 multiplied by 2 would be 174.
Subtract 174 from 368 to get 194.
194 divided by two equals 97.
To check,
97 plus 97 equals 194.
87 plus 87 equals 174.
174 plus 194 equals 368, the perimeter.
the first term in the sequence is 38. each following term is found by subtracting 7 in the previous term. find the third term?
Answer:
24
Step-by-step explanation:
This is a simple sequence, and they are asking only for the third number in the sequence, so repeated subtraction using is the optimal method for solving for the final answer.
First start with the first term in the sequence, which is 38. The next term is found by subtracting 7.
2nd term = 1st term - 7 (original equation)
2nd term = 38 - 7 (substitute values)
2nd term = 31 (combine like terms by subtracting)
Then repeat this process to find the third term.
3rd term = 2nd term - 7 (original equation)
3rd term = 31 - 7 (substitute values)
3rd term = 24 (combine like terms by subtracting)
Therefore the third term is 24.
What is the surface area of the triangular pyramid shown?round to the nearest tenth.
Answer:
57.6 cm/mm/m/in/ft squared
Step-by-step explanation:
You will need to answer the each triangle separately which you have to use the formula 1/2*b*h
5.2*1/2(6) = 15.6
4*1/2(6) = 12
5*1/2(6) = 15*2 (2 sides)
total = 57.6 cm/mm/m/in/ft squared
hope this helps
Express this number in standard form.
9.647 x 10^7= ?
Answer: 9647
Step-by-step explanation:
Answer:
9647000
Step-by-step explanation:
70 divided by the ratio 3:2
Answer:
42 : 28
Step-by-step explanation:
Sum the parts of the ratio , 3 + 2 = 5
Divide 70 by 5 to find the value of one part of the ratio
70 ÷ 5 = 14 ← value of 1 part of ratio, thus
3 parts = 3 × 14 = 42
2 parts = 2 × 14 = 28
70 divided in the ratio 3 : 2 is 42 : 28
What is the missing length?
Answer:
The answer to your question is 7 in
Step-by-step explanation:
Data
base = 14 in
area = 98 in²
Formula
Area of a parallelogram = base x height
-Solve for height
height = Area of a parallelogram / base
-Substitution
height = 98 / 14
-Simplification
height = 7 in or p = 7 in
-Conclusion
The length of p = 7 in
Edgar is getting better at math. On his first quiz he scored 57 points, then he scores 61 and 65 on his next two quizzes. If his scores continued to increase at the same rate, what will be his score on his 9th quiz? Show all work.
Answer:
His score is increasing by four each time, so on his 9th quiz, his score will be 89
hope that helps!
Step-by-step explanation:
Answer:
no wonder is was crawlin thiw um
Step-by-step explanation:
becsuse swear to god no winder
Solve for x. 8^(x+3)=32
Answer:
x = -4/3
Step-by-step explanation:
8^(x+3)=32
2^3 = 8
2^5 = 32
3( x + 3 ) = 5
3x + 9 = 5
3x = -4
x = -4/3
Tell me if I am wrong.
Can I get brainliest
Answer: x= -1 1/3 as a mixed number
Step-by-step explanation:
Volume of a hemisphere when radius is 2.5?
Answer:
that is the solution to the question
What is 87.5% of 8?
Answer:
7
Step-by-step explanation:
Convert 87.5% to a decimal.
87.5%/100%=.875
Multiply it with 8 to get 7
.875*8=7
Answer:
7
Step-by-step explanation:
Which triangle has hypotenuse Side A E?
A cube. The top face has points G, B, C, F and the bottom face has points H, A, D, E.
triangle BAE
triangle CAE
triangle GAE
triangle HAE
Answer: correct answer is triangle HAE
Step-by-step explanation:
Which of the following are properties of the circumcenter of a triangle? Check all that apply.
Answer:A B D
Step-by-step explanation:
B, circumcenter of an acute triangle is inside of it, the circumcenter of an obtuse triangle is outside of it, and the circumcenter of a right triangle is on the hypotenuse. C, Thats the definition. D, it also goes with C.
3(2x + 11) and (3x + 15)(2)
Answer:
3(2x+11)= 6x+33 and (3x+15)(2) = 6x+30
Step-by-step explanation:
Use distributive property to multiply the outside factor to each factor inside the parenthesis.
3(2x+11)
(3*2x)+(3*11)
6x+33
No, the given expressions 3(2x + 11) and (3x + 15)(2) are not equivalent.
Used the concept of distributive property that states,
The distributive Property States that when a factor is multiplied by the sum/addition of two terms, it is essential to multiply each of the two numbers by the factor, and finally perform the addition operation.
Given that the expressions are,
3(2x + 11) and (3x + 15)(2)
Now apply the distributive property in each expression,
3(2x + 11)
(3 × 2x) + (3 × 11)
6x + 33
(3x + 15)(2)
(3x × 2) + (15 × 2)
6x + 30
Therefore, both expressions are not equivalent.
To learn more about the distributive property visit:
https://brainly.com/question/2807928
#SPJ6
The complete question is,
Identify the equivalent expression,
3(2x + 11) and (3x + 15)(2)
What is the length of AB in the figure below?
Answer:
G. sqrt (74)
Step-by-step explanation:
Use the Pythagorean theorem to find AB, which is represented by c in the theorem.
a^2 + b^2 = c^2
7^2 + 5^2 = c^2
49 + 25 = c^2
74 = c^2 (Take the square root of each side)
c = sqrt (74)
So, AB = sqrt (74)
Length AB is an illustration of Pythagoras theorem.
The length of AB is (G) [tex]\mathbf{\sqrt{74}}[/tex]
The given figure is a right-angled triangle.
Such that:
AC = 7
BC = 5
AB = ?? The hypotenuse
Using Pythagoras theorem, we have:
[tex]\mathbf{AB^2 = AC^2 + BC^2}[/tex]
Substitute values for AC and BC
[tex]\mathbf{AB^2 = 7^2 + 5^2}[/tex]
Evaluate squares
[tex]\mathbf{AB^2 = 49 + 25}[/tex]
Add
[tex]\mathbf{AB^2 = 74}[/tex]
Take square roots
[tex]\mathbf{AB = \sqrt{74}}[/tex]
Hence, the value of AB is (G) [tex]\mathbf{\sqrt{74}}[/tex]
Read more about Pythagoras theorem at:
https://brainly.com/question/15138986
here's a hard one! What is 2+2+2-6 :0
Answer:
0
Step-by-step explanation:
2 plus 2 is 4 then you add 2 which makes 6 then subtract 6 to get the answer of 0.
Can some help me with this please.
Evaluate (5x – 4y) = z2 when x = 4, y = 1, and z = 3.
Step-by-step explanation:
= ( 5x - 4y) = z2
Putting the values given
= 5 (4) - 4(1) = (3)2
= 20 - 5 = 6
= 15 = 6
= 15 - 6
= 9
Consider ΔABC, where ∠C = 90° and ∠A + ∠B = 90°. Click on the statements that are true about the relationships of the angles Angles A and B are complementary angles. If sin A ≈ 0.766, then sin B ≈ 0.766. If sin A ≈ 0.766, then cos B ≈ 0.766. If cos B ≈ 0.766, then the sin A ≈ 0.766,
Answer: Angles A and B are complementary angles
If Sin A ≈ 0.766 then Cos B ≈ 0.766.
If Cos B ≈ 0.766 then Sin A ≈ 0.766
Step-by-step explanation: In any given right angled triangle, one angle measures 90 degrees while the addition of the other two angles equals to 90 degrees. Hence if angle C is given as 90 degrees, then angles A and B added together equals 90 degrees (complementary angles equal 90 degrees).
Also, Sin A cannot be the same value as Sin B, since angle A and angle B are not equal in measurement. However, being complementary, the Sin of angle A equals the Cos of angle B.
If Sin A ≈ 0.766, then angle A ≈ 50 degrees
That makes angle B equal to 40 degrees. The Cos of B ≈ 0.766
Therefore if Sin A ≈ 0.766, then Cos B ≈ 0.766
If Cos B ≈ 0.766 then Sin A ≈ 0.766 are both correct
With one mighty swipe of his sword, the knight cut off the flying dragon's head. If the dragon's head weighed 56.7 kg, how much force was used by the head to fall to the ground?
Answer:
The force used to fall by the head is
556.3N
Step-by-step explanation:
Given the the dragon's head has a mass m=56.7kg
Let us assume the acceleration due to gravity of the dragon's head is
9.81m/s^2
We know that the force
F=m*g
Substituting our data into the expression we have
F= 56.7*9.81
F= 556.2N
There are 12 white shirts, 8 blue shirts, and 6 red shirts on a rack. Which colors have a ratio of 3:4?
Answer:
8:12 or blue to white
I hope this helps! If it does, please mark brainliest UwU
What is s
1 /2 s + 38 = 1642
Step-by-step explanation:
1/2s+38=1642
0.5s=1642-38
s=1604/0.5
s=3208
Solve for x: -4x - 4 = -4(x + 2)
Answer:
no solution
Step-by-step explanation:
-4x - 4 = -4(x + 2)
Distribute
-4x -4 = -4x -8
Add 4x to each side
-4x+4x - 4 = -4x+4x -8
-4 = -8
This is never true so there is no solution
Hi I was wondering if I could get help on this please
Answer:
B
Step-by-step explanation:
The equation of line is y=-1/2 x+3 as it takes the form of y=mx+c
From this, the graph having gradient of -1/2 then the line will run from left to right. This eliminates options A and D
The pictures are not clear but we must ensure where the line crosses y intercept, the value of y should be 3 hence the only graph having these properties is option B.
Evaluate x-2 for x = -3.
Answer:
-5
Step-by-step explanation:
plug -3 into the equation (x)-2
-3-2=-5 if you subtract a number from a negative you will get a negative.
-5
Answer:
-5
Step-by-step explanation:
You plug in the value of -3 in the place of x, which gives you the equation of -3-2. You would then solve by subtracting 2 from -3, which gives you -5
Briana is looking at the nutrition information on a bag of popcorn. According to the label, a single serving is 1/6 of the bag. How many servings are there in 4 bags?
Answer:
There are 2/3 of the content as servings in 4 bags
Step-by-step explanation:
In this question, we are asked to calculate the amount of servings in 4 bags
From the question, we can see that the amount of servings in a single bag is 1/6 of the bag.
Now the number of servings in 4 bags will be mathematically equal to ; 1/6 + 1/6 + 1/6 + 1/6 = 4 * 1/6 = 4/6 = 2/3
This means that in 4 bags, 2/3 of the total content is the servings
Renee is sewing a quilt whose pattern contains right triangles. Each quilt piece has a height of 6 inches. And an area of 24 inches. How long is the base of each quilt piece?
Answer:
Base of quilt is 8 inch.
Step-by-step explanation:
Refer to the attachment.
Given that pattern on the quilt is right angle triangle. Consider ΔABC as right angle triangle where ∠ABC=90°.
Given that area of triangle is 24 in² and height is 6 inch that is, AB = 6 inch.
To find the base use formula for area of right angle triangle.
[tex]Area\:of\:triangle=\dfrac{1}{2}\times base\times height[/tex]
Substituting the values,
[tex]24=\dfrac{1}{2}\times base\times 6[/tex]
Simplifying,
[tex]24=\dfrac{6}{2}\times base[/tex]
Multiplying both sides by [tex]\dfrac{2}{6}[/tex],
[tex]24\times \dfrac{2}{6}=\dfrac{6}{2}\times base\times \dfrac{2}{6}[/tex]
Simplifying,
[tex]24\times \dfrac{2}{6}=base[/tex]
Dividing the numbers,
[tex]8=base[/tex]
Therefore, length of base of each quilt piece is 8 inch.
The sum of 7 and 2 in simplest form is _____.
Answer:
The sum of 7 and 2 in simplest form is 9
Step-by-step explanation:
7+2=9
I don’t understand what to do with this one
Answer:
1 2/3
Step-by-step explanation:
Change the mixed number to an improper fraction
5 5/6 = (6*5+5)/6 = 35/6
Multiply the improper fraction by the fraction
5 5/6 * 2/7
35/6 * 2/7
70/42
Divide the top and bottom by 14
5/3
Changing back to a mixed number
3/3 +2/3
1 2/3